TINJAUAN MIGRASI PENDUDUK DESA-KOTA, URBANISASI DAN DAMPAKNYA - Suko Bandiyono; Ken F. lndrawardani (Jurnal Kependudukan Indonesia, 2010)
Based on the overview of several socio-demographic publications, this paper examine the issue of rural-urban migration and the consequences of urbanization. Urbanization is a complexs phenomenon which strongly determined of rural-urban migration. Migration to large metropolitan cities from rural areas and small towns has put enormous pressure in place of destination and created many sosio-economic and demographic problems. Metropolitan cities has becomed the consentration of urban poor which mostly holds the informal jobs and live in squatter areas.Keywords: Rural-urban migration, urbanization, sosial and demographic impacts